Endogenous growth hormone (GH)-releasing hormone is required for GH responses to pharmacological stimuli. - Jaffe, C A (1996)
The roles of hypothalamic growth hormone-releasing hormone (GHRH) and of somatostatin (SRIF) in pharmacologically stimulated growth hormone (GH) secretion in humans are unclear. GH responses could result either from GHRH release or from acute decline in SRIF secretion. To assess directly the role of endogenous GHRH in human GH secretion, we have used a competitive GHRH antagonist, (N-Ac-Tyr1,D-Arg2)GHRH(1-29)NH2 (GHRH-Ant), which we have previously shown is able to block the GH response to GHRH. We first tested whether an acute decline in SRIF, independent of GHRH action, would release GH. Pretreatment with GHRH-Ant abolished the GH response to exogenous GHRH (0.33 microgram/kg i.v.) but did not modify the GH rise after termination of an SRIF infusion. We then investigated the role of endogenous GHRH in the GH responses to pharmacologic stimuli of GH release. The GH responses to arginine (30 g i.v. over 30 min), L-dopa (0.5 g orally), insulin hypoglycemia (0.1 U/Kg i.v.), clonidine (0.25 mg orally), or pyridostigmine (60 mg orally) were measured in healthy young men after pretreatment with either saline of GHRH-Ant 400 microgram/kg i.v. In every case, GH release was significantly suppressed by GHRH-Ant. We conclude that endogenous GHRH is required for the GH response to each of these pharmacologic stimuli. Acute release of hypothalamic GHRH may be a common mechanism by which these compounds mediate GH secretion.